714 PD1 x TGFβR2 bispecifics selectively block TGFβR2 on PD1-positive T cells, promote T cell activation, and elicit an anti-tumor response in solid tumors. (9th November 2020) - Moore, Gregory; Schubbert, Suzanne; Bonzon, Christine; Avery, Kendra; Rashid, Rumana; Pong, Erik; Ochyl, Lukasz; Nisthal, Alex; Chu, Seung; Ernst, James; Desjarlais, John
Abstract : Background: TGFβ production by solid tumors and their microenvironment is a major mechanism used by tumors to avoid immunosurveillance. Blockade of TGFβ has been shown to promote an anti-tumor response; however, systemic blockade of TGFβ has also been associated with toxicity. We hypothesized that a PD1 x TGFβR2 bispecific antibody could selectively block the suppressive activity of TGFβ on tumor T cells and enhance their anti-tumor activity while avoiding the toxicity associated with systemic blockade. Methods: We engineered bispecific antibodies that simultaneously engage PD1 and TGFβR2 using Xencor's XmAb platform. The anti-TGFβR2 arm was tuned for optimal activity by introducing affinity-modulating amino acid substitutions. The activity of PD1 x TGFβR2 bispecifics was evaluated in vitro using a signaling assay to measure phosphorylated SMAD (pSMAD) by flow cytometry with exogenous TGFβ in unactivated and activated PBMC. In vivo activity was evaluated by monitoring the engraftment of human PBMC in NSG mice (huPBMC-NSG). Anti-tumor activity was assessed in huPBMC-NSG mice engrafted with established human cancer cell lines. Antibodies against other T cell targets were also incorporated into TGFβR2 bispecifics, and similarly evaluated in vitro and in vivo. Results: PD1 x TGFβR2 bispecifics were confirmed to bind PD1 and block binding of TGFβ to TGFβR2. In vitro, we found that T cells from activated, serum-deprived PBMC exhibited robust induction of pSMAD in response to TGFβ, and PD1 x TGFβR2 bispecifics selectively inhibited pSMAD induction in PD1-positive T cells as demonstrated by over a 100-fold potency increase compared to an untargeted anti-TGFβR2 control. Additionally, we saw an enhancement of potency when evaluating blocking activity in activated (PD1-high) vs. unactivated (PD1-low) T cells. Similar selectivity was measured when comparing inhibition of pSMAD induction for activated T cells versus other PD1-negative, TGFβ-responsive immune cells. Intriguingly, TGFβR2 bispecifics incorporating antibodies against other T cell targets allowed for the targeting of a broader population of T cells while still conferring potent selectivity against target-negative cells. In vivo, treatment of huPBMC-NSG mice with TGFβR2 bispecifics promoted superior T cell engraftment and combined additively with PD1 blockade. Furthermore, TGFβR2 bispecific treatment of huPBMC-NSG mice containing established MDA-MB-231 triple-negative breast cancer tumors promoted an anti-tumor response that was also augmented with PD1 blockade. Conclusions: Multiple PD1 x TGFβR2 bispecifics were engineered to selectively block TGFβR2 on PD1-positive T cells and evaluated in vitro and in vivo. Compelling activity, including additivity with PD1 blockade, suggests that clinical development is warranted for the treatment of human malignancies.